2010
DOI: 10.1007/s10495-010-0565-x
|View full text |Cite
|
Sign up to set email alerts
|

Betanodavirus up-regulates chaperone GRP78 via ER stress: roles of GRP78 in viral replication and host mitochondria-mediated cell death

Abstract: Whether viral pathogens that induce ER stress responses benefit the host or the virus remains controversial. In this study we show that betanodavirus induced ER stress responses up-regulate GRP78, which regulates the viral replication and host cellular mitochondrial-mediated cell death. Betanodavirus (redspotted grouper nervous necrosis virus, RGNNV) infection resulted in the following increased ER stress responses in fish GF-1 grouper fin cells: (1) IRE-1 and ATF-6 sensors at 48 h post-infection (p.i.) that u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 60 publications
7
30
2
Order By: Relevance
“…Since, A. hydrophila displays wide host specificity it would be interesting to see whether same pathogenic mechanisms are employed across other host species. Microbe-induced ER-stress and UPR has been reported in fish37 and mammals3638394041. Our study not only extends these findings to A. hydrophila but further suggests UPR to be an evolutionarily conserved pathological mechanism.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Since, A. hydrophila displays wide host specificity it would be interesting to see whether same pathogenic mechanisms are employed across other host species. Microbe-induced ER-stress and UPR has been reported in fish37 and mammals3638394041. Our study not only extends these findings to A. hydrophila but further suggests UPR to be an evolutionarily conserved pathological mechanism.…”
Section: Discussionsupporting
confidence: 83%
“…While eIF2α halts translation of new proteins in ER and is implicated in apoptosis, BiP acts as pro-survival factor under different stress conditions36. Earlier reports implicated ER-stress and BiP expression to be critical in betanodavirus-induced apoptosis in fish cells37. We wondered the elevated expression of the three ER-stress markers have any correlation with A. hydrophila -induced HKM apoptosis.…”
Section: Discussionmentioning
confidence: 91%
“…UPR is an evolutionarily conserved response that can be activated to enhance the protein-folding capacity of the ER and promote ER-associated protein degradation to remove the misfolded proteins. Therefore, the release of GRP-78 is critical in the early protective response, which is an upstream gene in the ERS signaling and can also be seen as a marker in the early ERS [15]. In our study, the increased mRNA and protein expression of GRP-78 induced by I/R demonstrated the process of ERS, which can protect the ER and further maintain ER homeostasis.…”
Section: Discussionmentioning
confidence: 61%
“…In contrast, the betanodavirus B2 protein appears to function as a suppressor of host siRNA silencing [12,13] or as a EDITORIAL necrotic death factor [14,15] . In addition, red-spotted grouper nervous necrosis virus (RGNNV) infection and expression can trigger the ER stress response, which results in the upregulation of the 78 kDa glucose regulated protein at the early replication stage [16] . Very recently, RGNNV has been shown to induce the production of reactive oxygen species (ROS) during the early and middle replication stages [17] .…”
Section: Betanodavirusmentioning
confidence: 99%
“…In our fish system, we found that RGNNV infection can induce downregulation of the anti-apoptotic Bcl-2 genes at the middle apoptotic stage (48 h p.i.) [16] . Subsequently, mitochondrial damage and RGNNV-induced necrotic cell death were assessed in stable cell lines producing the anti-apoptotic Bcl-2 proteins, zfBcl-xL or zfMcl-1a.…”
Section: Bcl-2 Family Members During Betanodavirus Infectionmentioning
confidence: 99%